Russian constructions with ‘take’ expressing an unexpected event: Their historical origin and development in the 19th century - Weiss, Daniel (Stellenbosch Papers in Linguistics Plus, 2022)
This study aims at elucidating the rise and expansion of four competing Russian constructions expressing the unexpectedness of an event. Тhree of them are built according to the pseudo-coordinative model ‘take and do’ and one follows the serial model ‘take do’. The historical data stemming from the Russian national corpus and covering the whole 19th century reveals striking differences between these constructions in terms of frequency and grammaticalisation, the most peripheral being the serial model. Evidence for ongoing grammaticalisation is mainly based on the rise of non-canonical second verbs denoting an uncontrollable event and inanimate subjects. Special attention will be given to the meanings of the imperative and contextually bound pragmatic effects.